Strengthening Indonesia’s Beef Supply Chain Resilience: Strategic Business Model Development For Cattle Fattening - Wibisono Chandra; R. Nunung Nuryartono; Yandra Arkeman; Zenal Asikin (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: Indonesia’s beef feedlot industry plays a strategic role in national food security; however, it remains constrained by persistent feed shortages, fragmented supply chains, and inconsistent regulatory frameworks. Existing studies have examined these challenges separately but have not produced an integrated strategic business model that aligns policy, technology, markets, and multi-stakeholder collaboration to address them.Purpose: This study aims to develop a Strategic Business Model Canvas (SBMC) to improve the resilience, sustainability, and competitiveness of Indonesia’s feedlot industry by integrating policy coherence, technological adoption, market strengthening, and Quadruple Helix collaboration.Design/methodology/approach: A qualitative, field-based design was employed using expert interviews, open-ended questionnaires, field observations, and policy document analysis. Data were collected from 20 key stakeholders representing government, industry, academia, and farmer groups across East Java. Open and axial coding were used to identify systemic bottlenecks, which were then mapped into the SBMC framework and validated through methodological triangulation.Findings/Result: Four structural constraints were identified—feed availability gaps, supply chain inefficiencies, regulatory fragmentation, and weak stakeholder coordination. The proposed SBMC introduces strategic levers including local feed innovation, digital traceability, improved breeder–feedlot integration, and cross-sector partnerships. These mechanisms enhance value creation, reduce import dependency, and strengthen system resilience in line with ESG-oriented agribusiness transformation.Conclusion: The SBMC developed in this study provides a theory-informed and stakeholder-validated framework that bridges policy design and operational realities in Indonesia’s feedlot sector. It offers a practical roadmap for achieving a more inclusive, resilient, and sustainable beef supply chain.Originality/value (State of the art): This study is the first to develop an empirically grounded SBMC for the Indonesian feedlot industry by integrating the Quadruple Helix model with strategic dimensions of policy, market, technology, and governance. It provides a comprehensive transformation framework with clear operational implications for achieving national food sovereignty. Keywords: food sovereignty, inclusive agribusiness, Indonesia beef cattle industry, strategic Business Model Canvas (SBMC), quadruple helix collaboration